LRS Bianchi Type-I Cosmological Model in Modified f(R, T) Gravitation Theory filled with Perfect Fluid - Ingle, Vishal; Mete, Vijay G. (The Nucleus, 2025)
This study explores LRS Bianchi Type-I space time filled with a perfect fluid within the framework of f(R,T) gravity, where R represents the Ricci scalar and T denotes the trace of the stress-energy momentum tensor. We analyze the simplest form of cosmic evolution in the context of general non-minimally coupled gravity models. Two specific models of f(R,T) gravity are considered. A time-dependent deceleration parameter is introduced, leading to an accelerated universe with an exact field solution. Additionally, we examine the kinematical and physical properties of the proposed models.